Optimalisasi Peran Lembaga Amil Zakat Masjid Agung Al-Azhar Dalam Pendistribusian Bantuan Kemanusiaan Bagi Korban Bencana Alam - Saputra, Wahidin (Jurnal Manajemen Dakwah, 2025)
The Zakat Collection Institution (LAZ) has very vital role in effort management of zakat, infak and alms (ZIS) funds collected from community. The funds No only distributed For interest social religion and empowerment economy people, but also used in a way strategic in context countermeasures disaster. One of the form real LAZ's contribution is his involvement in give help humanity to affected communities disaster nature, such as earthquake earth, flood, eruption mountain fiery, until land landslide. LAZ Al Azhar Grand Mosque is one of the active institution in activity responsive disaster said. Through network volunteers and its humanitarian programs, LAZ Al Azhar has play a role in distribution logistics, services health, provision need principal, and support recovery psycho-social for the disaster victims. This article aiming For review in a way in depth the strategies implemented by LAZ Al Azhar Grand Mosque in optimize the distribution process help. Some aspects discussed covers efficiency operational, speed distribution, accuracy targets, and effectiveness of the program in term short and also long. In addition, the article this also highlights challenges that often arise in implementation activities in the field, such as constraint logistics, limitations power volunteers, and the lack of coordination inter-agency. Use technology information, system digital reporting, as well as collaboration cross sector exposed as solution potential in increase transparency, accountability, and sustainability of the aid programs run by LAZ.  Keywords: Zakat Collection Institution, Assistance Humanity, Natural Disasters, Optimization, Transparency, Alms, Charity.